Beatrice Cenci in Hawthorne, Melville and her Atlantic-Rim Contexts - Long Hoeveler, Diane (Romanticism on the Net, 2005)
AbstractThe figure of Beatrice Cenci was, according to Melville, the embodiment of those “two most horrible crimes possible to civilized humanity--incest and parricide." Nevertheless, she enjoyed a curious popularity as a subject in late eighteenth and nineteenth-century Atlantic-rim literary culture. Indeed, the renewed fascination with her story indicates several important psychological as well as social themes that authors as diverse as Walpole, Shelley, Swinburne, Hawthorne, Melville, Dickens, and Wharton all attempted to delineate. Although critics have analyzed the Cenci figure in Pierre and The Marble Faun before, comparing the use of this motif in relation to the earlier British works allows us a different perspective on an obvious though neglected theme in the two novels. In addition, the focus on the Cenci narrative in Atlantic-rim culture allows us to examine how a representation crosses cultures, nationalities, and ideologies in order to articulate common concerns and anxieties.In British gothic works the representation of Beatrice speaks to the horrific and corrupt power of the mother and father, both as brutal governmental force, an insane ruler, and a despotic and sadistic mater or pater familias, the head of the corrupted and polluted family. Further, the spectre of incest (sibling and parental) that stalks British gothic and romantic texts speaks to an ideologically conflicted posture. In works by Byron and Shelley, sibling incest is sometimes idealized (i.e., Manfred or Laon and Cythna), while in Shelley’s The Cenci incestuous rape by the father of his daughter (with broad suggestions of sodomy as well) is the most pernicious and evil act that can be committed. Clearly, the British romantics were of a divided mind about incest as a literary trope for the reunion of self and other.By the time the Cenci legend transmutes and reappears in America, however, Melville and Hawthorne are placing even heavier weight on the representation and its associations. Both of their works ask the questions: What is the nature of human history? What power does the past hold over the present and the future? Can Americans overthrow their European heritage and establish a new Garden in America, or is that promise blasted and futile? Both Pierre and The Marble Faun, although different from each other in their treatments of human nature and society, are particularly American works in criticizing the notion that a new order can replace the corrupt and rejected world of the fathers. Whereas Shelley's play ultimately condemns Beatrice for revenge on her father, neither Melville nor Hawthorne’s works do, although both see her as an omen predicting the failure of America to achieve its original promise.